Decrease of Klotho in the Kidney of Streptozotocin-Induced Diabetic Rats. (27th June 2010) - Cheng, Meng-Fu; Chen, Li-Jen; Cheng, Juei-Tang
Abstract : The klotho gene is expressed in a limited number of tissues, most notably in distal convoluted tubules in the kidney and choroid plexus in the brain. A previous study suggested that Klotho increases resistance to oxidative stress. However, changes of Klotho expression in high glucose-induced oxidative stress remain unclear. In the present study, we used streptozotocin-induced diabetic rats (STZ rats) to examine the effects of insulin, phloridzin or antioxidant, tiron on diabetic nephropathy. Both insulin and phloridzin reversed the lower Klotho expression levels in kidneys of STZ rats by the correction of hyperglycemia. Also, renal functions were improved by these treatments. In addition to the improvement of renal functions, the decrease of Klotho expression in kidney of STZ rats was also reversed by tiron without changing blood glucose levels. The reduction of oxidative stress induced by high glucose can be considered for this action of tiron. This view was further confirmed in vitro using high glucose-exposed Madin-Darby canine kidney (MDCK) epithelial cells. Thus, we suggest that decrease of oxidative stress is not only responsible for the improvement of renal function but also for the recovery of Klotho expression in kidney of STZ rats.